2000
DOI: 10.1097/00000658-200009000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Does Prophylactic Octreotide Decrease the Rates of Pancreatic Fistula and Other Complications After Pancreaticoduodenectomy?

Abstract: These data demonstrate that the prophylactic use of perioperative octreotide does not reduce the incidence of pancreatic fistula or total complications after pancreaticoduodenectomy. Prophylactic octreotide use in this setting should be eliminated, at a considerable cost savings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
378
5
12

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(409 citation statements)
references
References 26 publications
14
378
5
12
Order By: Relevance
“…Amongst all, texture of the gland remains the most important predictive factor. The soft and fatty texture of the pancreas [38][39][40][41][42][43][44][45][46] with a non dilated duct (duct size < 3 mm) [45,46] has a higher incidence of fistula when compared to fibrotic/atrophic pancreas with a dilated duct. Increased secretion of pancreatic juice is seen in patients with soft or normal pancreatic remnant and is associated with increased rates of POPF [41].…”
Section: Organ and Disease Related Factorsmentioning
confidence: 99%
“…Amongst all, texture of the gland remains the most important predictive factor. The soft and fatty texture of the pancreas [38][39][40][41][42][43][44][45][46] with a non dilated duct (duct size < 3 mm) [45,46] has a higher incidence of fistula when compared to fibrotic/atrophic pancreas with a dilated duct. Increased secretion of pancreatic juice is seen in patients with soft or normal pancreatic remnant and is associated with increased rates of POPF [41].…”
Section: Organ and Disease Related Factorsmentioning
confidence: 99%
“…
W175as "drain output of any measurable volume of fluid on or after postoperative day 3 with an amylase content greater than three times the serum amylase activity" [11].The overall rate of pancreatic fistula after pancreaticoduodenectomy ranges from 17% in patients in whom the pancreatic remnant has a hard consistency [12] and exocrine pancreatic function and pancreatic juice output are impaired [13] to 25% in cases in which the pancreas is soft [1], that is, the parenchyma is normal [13]. Soft pancreatic texture [1,3,13] and small pancreatic duct size [3] are the most important preoperative risk factors for the development of pancreatic fistula.

The diagnosis of pancreatic fistula usually is made an average of 7 days after pancreaticoduodenectomy [5,14,15].

…”
mentioning
confidence: 99%
“…Soft pancreatic texture [1,3,13] and small pancreatic duct size [3] are the most important preoperative risk factors for the development of pancreatic fistula.The diagnosis of pancreatic fistula usually is made an average of 7 days after pancreaticoduodenectomy [5,14,15]. Pancreatic fistula diagnosed with repeated assays of pancreatic enzymes in peripancreatic fluid drainage [11,14,16] © American Roentgen Ray Society P ancreaticoduodenectomy is safe in the management of various malignant and benign diseases of the pancreatic head and periampullary region.…”
mentioning
confidence: 99%
“…In 2011, Kuroki et al [14] found no significant difference in the incidence of any grade POPF (34.5% stented vs. 40.9% non-stented, P=NS) or clinically significant POPF (21.7% stented vs. 27.3% non-stented, P=NS) among patients with a soft pancreatic remnant utilizing the external duct stent following PD. This suggests that while a soft pancreatic texture is a well-documented risk factor for POPF formation [15][16][17][18][19], pancreatic duct stenting has no effect on mitigating that risk.…”
Section: Discussionmentioning
confidence: 99%